The effects of punishment on the offenders’ relatives: Difficulties and discussion regarding their problematization at the sentencing stage - de Saussure, Sophie (Criminologie)

(untitled) (Les Presses de l’Université de Montréal, 2022)
This paper looks at the problematization of the effects of punishment on offender’s relatives, specifically at the sentencing stage. To do this, we discuss the way modern criminal law organizes the absence of offenders’ relatives and the reasoning that contributes to creating and solidifying this absence. We also look at how, in the background, some acknowledgment of the effects of absence takes place and affects the reasoning behind maintaining absence, reasoning that still dominates thought and practice in penal matters. Finally, we show that exposing the effect of absence and recognizing the possibility of overcoming it could contribute to informing and modifying this reasoning, making it possible to build a more inclusive system of criminal law.